Perceived social isolation, social disconnectedness and falls: the mediating role of depression. (27th May 2021) - Quach, Lien T.; Burr, Jeffrey A.
Abstract: Objectives: to estimate the association of social disconnectedness and perceived social isolation with the risk of falls and also investigate whether depression mediated this association. Method: Biennial longitudinal survey data from 2006 to 2012 waves of the U.S. Health and Retirement Study of adults aged 65 and older (N = 22, 153 observations) were examined. The outcome variable was number of self-reported falls over the observation period. Independent variables included social isolation (social disconnectedness, perceived social isolation) and number of depressive symptoms. Generalized Estimating Equation regressions were performed to address the research questions. Results: Regression models indicated that social disconnectedness is associated with a 5% increase in the risk of falls. Perceived social isolation (lack of perceived social support and loneliness combined) was associated with a 33% increase in falls risk. For each increase in the number of depressive symptoms, the risk of falls increased by 13%. Also, the number of depressive symptoms mediated the association between perceived social isolation and risk of falls. Conclusion: Our findings were suggestive of the need to consider social isolation when designing falls prevention programs. More research is needed with research designs that address potential endogeneity bias.